Strategic Management of Mineral Resources in China: Economic, Environmental, and Policy Perspectives - Qiu, Wang; Abdul Latiff, Ahmed Razman (International Journal of Engineering and Management Research, 2026)
This study examines the strategic management of mineral resources in China, integrating economic, environmental, and policy perspectives. Using a mixed-methods approach, we analyze the economic impacts, environmental sustainability, and policy frameworks governing mineral resource management in China. Our findings highlight the critical role of corporate governance, sustainable practices, and policy innovations in enhancing the efficiency and sustainability of mineral resource management. We propose a comprehensive framework that balances economic growth with environmental protection, offering actionable insights for policymakers and industry stakeholders. This study contributes to the literature by providing a detailed analysis of the Chinese context, identifying gaps in current practices, and suggesting future directions for sustainable resource management.